Comparison of primary and delayed wound closure of dog-bite wounds - Xiaowei, Z.; Wei, L.; Xiaowei, H.; Yunbei, X.; Zhenhua, L.; Yeqing, Y.; Jiaqi, Y.; Chuanlin, W. (Veterinary and Comparative Orthopaedics and Traumatology, 2013)
Background: Primary bite wound suturing in the emergency department remains controversial in some cases.Objective: We conducted a study to investigate the infection rate and cosmetic appearance between primary wound closure and delayed wound closure in dog bite wounds in humans.Methods: All patients with bite wounds were treated with oral antibiotic medications. We adopted a randomized cohort study, dividing the patients who needed wound closure into two groups: 60 patients for primary closure, and 60 patients for delayed closure, and compared the infection rate and wound cosmetic appearance scores.Results: In the primary closure group, four people (6.7%) developed a wound infection without systemic infection. In the delayed closure group, three people (5%) developed a wound infection (p = 0.093), but there were not any patients that developed a systemic infection. Thirty-three patients (55%) in the primary closure group had optimal cosmetic scores, whereas 20 patients (33.3%) in the delayed closure group had optimal cosmetic scores (p = 0.012).Conclusion: Although primary wound closure for dog bites may be associated with a higher infection rate, the cosmetic appearance after primary closure was still acceptable.
Keywords: wound infection; Dog bite; primary wound closure; delayed wound closure; cosmetic scale